Software Engineering Frameworks for the Cloud Computing Paradigm - Mahmood, Zaigham; Saeed, Saqib; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
With the emergence of cloud computing, traditional approaches to software engineering must be adapted in order to take full advantage of the benefits promised by cloud technologies. This timely and authoritative text/reference presents the latest research on Software Engineering Frameworks for the Cloud Computing Paradigm, drawn from an international selection of researchers and practitioners. The book offers both a discussion of relevant software engineering approaches and practical guidance on enterprise-wide software deployment in the cloud environment, together with real-world case studies. Topics and features: Presents the state of the art in software engineering approaches for developing cloud-suitable applications Discusses the impact of the cloud computing paradigm on software engineering, including the semantic web Offers guidance and best practices for students and practitioners of cloud-based applications architecture Examines the stages of the software development lifecycle, with a focus on the requirements engineering and testing of cloud-based applications Reviews the efficiency and performance of cloud-based applications Explores feature-driven and cloud-aided software design, presenting strategies for cloud adoption and migration Provides relevant theoretical frameworks, practical approaches and current and future research directions This practical and clearly-structured volume is an ideal self-study primer for students of cloud computing and software engineering. Software engineers, application developers and IT infrastructure managers will also find the work to be an invaluable reference. Dr. Zaigham Mahmood is a researcher in the School of Computing at the University of Derby, UK, and a Senior Technology Consultant at Debesis Education. His other publications include the successful Springer book Cloud Computing for Enterprise Architectures. Dr. Saqib Saeed is an Assistant Professor in the Computer Science Department at Bahria University, Islamabad, Pakistan.
Part I: Impact of the Cloud Paradigm on Software Engineering -- Impact of the Semantic Web and Cloud Computing Platforms on Software Engineering -- Envisioning Cloud-Induced Transformations in the Software Engineering Discipline -- Limitations and Challenges in Cloud-Based Applications Development -- Part II: Software Development Life Cycles for Cloud Platforms -- Impact of Cloud Services on Software Development Life Cycles -- Cloud-Based Development Using Classic Life Cycle Models -- Business Requirements Engineering for Developing Cloud Computing Services -- Testing Perspectives for Cloud-Based Applications -- Testing in the Cloud -- Part III: Software Design Strategies for Cloud Adoption -- Feature-Driven Design of SaaS Architectures -- Impact of Cloud Adoption on Agile Software Development -- Technical Strategies and Architectural Patterns for Migrating Legacy Systems to the Cloud -- Cloud-Aided Software Engineering -- Development of Cloud Applications in Hybrid Clouds with Support for Multi-Scheduling -- Part IV: Performance of Cloud-Based Software Applications -- Efficient Practices and Frameworks for Cloud-Based Applications Development -- A Methodology for Identifying the Relationships Between Performance Factors for Cloud Computing Applications.
Keywords: Computer science; Computer Communication Networks; Software engineering; Management information systems; Computer Science; Computer Communication Networks; Software Engineering; Business Information Systems